Ferric carboxymaltose assessment of morbidity and mortality in patients with iron deficiency and chronic heart failure (FAIR-HF2-DZHK05) trial: baseline characteristics and comparison to other relevant clinical trials - Anker, Stefan; Friede, Tim; Butler, Javed; Talha, Khawaja M.; Placzek, Marius; Diek, Monika; Nosko, Anna; Stas, Adriane; Kluge, Stefan; Jarczak, Dominik; Deheer, Geraldine; Rybczynski, Meike; et al. (European journal of heart failure, 2025)
Aims Prior randomized trials have reported conflicting evidence regarding the efficacy of intravenous (IV) iron in patients with heart failure with reduced ejection fraction (HFrEF) and iron deficiency (ID). Methods and results FAIR-HF2 is a double-blind, randomized, controlled trial evaluating the efficacy of IV ferric carboxymaltose in patients with HFrEF and ID. We report the baseline characteristics of enrolled patients and compare them with other major trials of IV iron in HFrEF (FAIR-HF, CONFIRM-HF, AFFIRM-AHF, IRONMAN, and HEART-FID). A total of 1105 patients were randomized between March 2017 and November 2023. Most patients were men (67%) and median age was 72 (interquartile range [IQR] 63-79) years. More than one-third had a heart failure hospitalization within the preceding 12 months (36%), and 53% were hospitalized at randomization. Common comorbidities included hypertension (79%), coronary artery disease (74%), dyslipidaemia (67%), and diabetes (46%). The median left ventricular ejection fraction was 58% (IQR 42-77) and mean estimated glomerular filtration rate was 58 (IQR 42-77) ml/min/1.73 m2. A total of 1064 (96%) patients were on renin-angiotensin system inhibitors (angiotensin receptor-neprilysin inhibitors [ARNI] 38%), 1016 (92%) on beta-blockers, and 779 (71%) on mineralocorticoid receptor antagonists; and 261 (24%) of patients were on sodium-glucose cotransporter 2 (SGLT2) inhibitors, which is much higher than prior trials. A higher proportion of patients had ischaemic HFrEF (78%) compared to preceding trials. The baseline median haemoglobin (g/dl) was 12.7 (IQR 11.8-13.4), median serum ferritin (μg/dl) was 63 (IQR 36-90), and median transferrin saturation (%) was 16.5 (IQR 11.8-22.9), resembling that of other trials. The mean 6-min walk distance at enrolment was 314 ± 118 m. Conclusion The FAIR-HF2 trial represents a contemporary cohort of patients with baseline characteristics mostly similar to prior trial populations. Use of SGLT2 inhibitors and ARNI in FAIR-HF2 was higher than in prior trials. Clinical Trial Registration: ClinicalTrials.gov ID NCT03036462.